The Principal's Leadership in Improving Teachers' Professional Competence at SDN - Tihabsah; Rahmat; Rofiq, Muhammad Husnur (Journal of Education and Learning Innovation, 2024)
Principals as leaders of educational institutions have a strategic role in improving teachers' professional competence. The purpose of this research is to find out: Principal program, program implementation, and obstacles encountered by principals in improving teachers' professional competence. This research uses a descriptive method with a qualitative approach. Data collection techniques were observation, interview, and documentation. The subjects of this study were principals, teachers, KKG leaders, school committees, supervisors, and outstanding teachers. The results of this study show that: 1) The principal's program in improving the professional competence of teachers by holding deliberations at the beginning of the school year with the vice principal, teachers, KKG chairman, school committee, supervisor, so that it shows good results, especially in improving the professional competence of teachers at SDN 26 Banda Aceh City 2) the implementation of the principal's program in improving the professional competence of teachers is by creating a conducive climate, providing opportunities for the development of teacher competence, 3) The obstacles faced by principals in improving the professional competence of teachers are that there are still teachers who have not mastered Computer Science Technology (ICT), and the lack of motivation provided by the family in improving professional competence so that it becomes an obstacle for teachers in preparing lesson planning and implementation.